Digitalisasi Dakwah Berbasis Artificial Intelligence: Analisis Hukum Islam Terhadap Penggunaan Aplikasi Berbasis AI Sebagai Media Dakwah Era Digital Perspektif Maqâshid Syarî’ah - Safdhinar Muhammad An Noor; Erfaniah Zuhriah; Syahril Siddik (EduInovasi: Journal of Basic Educational Studies, 2025)
The development of digital technology has had a significant impact on various aspects of life, including in the field of Islamic preaching. The use of Artificial Intelligence (AI)-based applications such as preaching chatbots, Islamic voice assistants, and religious content automation platforms has become a rapidly growing phenomenon in the digital era. This article aims to analyze the use of AI technology as a medium for preaching from the perspective of Islamic law with the Maqâshid Syarî'ah approach. This study uses a qualitative method with a normative-theological approach, through a literature study of relevant classical and contemporary literature. The results of the study show that the use of AI in preaching can be categorized as a wasîlah (means) whose law follows the purpose of its use. If AI is used to support the spread of Islamic values ​​that bring benefits, maintain religion (hifz al-dîn), and provide ease in accessing Islamic knowledge, then this is in accordance with the main objectives of Maqâshid Syarî'ah. However, the potential for information distortion, lack of authenticity of scientific chains, and minimal control over content produced by AI are challenges that need to be watched out for. Therefore, regulation and supervision of scholars and religious institutions are needed to ensure that AI-based digital da'wah remains within the corridor of sharia and ethics. In conclusion, AI technology can be a legitimate da'wah instrument according to sharia if it is managed with the principle of caution and sharia responsibility.